Development of Interactive E-LKPD Liveworksheets Based on Differentiated Instruction in IPAS Subjects Fifth Grade - Resha Mutia Fahrizy; Moh. Fathurrahman (Postgraduate, University of Mataram, 2024)
This research aims to produce Interactive Liveworksheets E-LKPD products based on Differentiated Instruction to improve science and science learning outcomes in class V of Cepoko State Elementary School. The output products developed are assessed in terms of the validity of the material and media content, practicality and effectiveness. This research uses R&D research with the Borg and Gall development model. The subjects in this research were fifth grade students at Cepoko State Elementary School, Semarang City. The data collection techniques used are test techniques in the form of pre-tests and post-tests as well as non-test techniques which include observation, interviews and documentation. The validation results by material and media expert validators show that the E-LKPD Interactive Liveworksheets Based on Differentiated Instruction is very suitable for use with a percentage of 93% from material expert validators and 100% from media expert validators. Meanwhile, the practicality of the media being developed is based on the average percentage of teacher response questionnaires of 98% and students of 89.5% on product trials in the very practical category. Based on the results of the pre-test and post-test, it is known that E-LKPD Interactive Liveworksheets Based on Differentiated Instruction can improve student learning outcomes. This is proven by the results of an increase in the average pre-test score from 53.46 to 83.08 in the post-test. Then the N-Gain test results obtained a score of 0.64 in the medium category.